Hypericum Perforatum-Derived Exosomes-Like Nanovesicles: A Novel Natural Photosensitizer for Effective Tumor Photodynamic Therapy - Ma X; Chen N; Zeng P; He Y; Zhang T; Lu Y; Li Z; Xu J; You J; Zheng Y; Wang L; Luo M; et al. (International Journal of Nanomedicine)
Xiaoyu Ma, Ni Chen, Peiyuan Zeng, Yuqian He, Tao Zhang, Yu Lu, Ziyu Li, Jin Xu, Jingcan You, Youkun Zheng, Liqun Wang, Mao Luo, Jianbo Wu Basic Medicine Research Innovation Center for Cardiometabolic Diseases, Ministry of Education; Laboratory for Cardiovascular Pharmacology, Department of Pharmacology, School of Pharmacy; Luzhou Municipal Key Laboratory of Thrombosis and Vascular Biology Southwest Medical University, Luzhou, 646000, People’s Republic of ChinaCorrespondence: Jianbo Wu, Basic Medicine Research Innovation Center for Cardiometabolic Diseases, Ministry of Education, Southwest Medical University, Luzhou, Sichuan, 646000, People’s Republic of China, Tel/Fax +0086-830-3161702, Email jbwucn1996@yahoo.comBackground: Natural photosensitizers hold potential for photodynamic therapy (PDT) but are often limited by poor visible light absorption. Plant-derived exosome-like nanovesicles offer an innovative platform for enhancing photosensitizer performance.Methods: Hypericum perforatum-derived nanovesicles (HPDENs) were characterized using electron microscopy, dynamic light scattering, and proteomic and miRNA sequencing. High-performance liquid chromatography confirmed hypericin content. PDT efficacy was assessed in vitro and in vivo.Results: HPDENs exhibited robust photosensitizing properties, generating reactive oxygen species (ROS) through both Type I and Type II pathways upon light activation. In vitro, HPDENs showed light dose-dependent cytotoxicity against human melanoma cells, characterized by elevated ROS production and apoptosis induction. In vivo, HPDEN-mediated PDT significantly suppressed tumor growth and induced extensive tumor necrosis, with no observable toxicity to major organs.Conclusion: HPDENs represent a novel plant-derived photosensitizer with dual ROS generation pathways and significant therapeutic efficacy, providing a promising platform for enhancing photodynamic therapy.Keywords: Hypericum perforatum-derived exosomes-like nanovesicles, photosensitizer, photodynamic therapy, reactive oxygen species, apoptosis